Brief Report: Differential Timing of Cholesterol Increase During Successful HCV Therapy. (1st August 2018) - Rivero-Juarez, Antonio; Camacho, Angela; Brieva, Teresa; Frias, Mario; Lopez-Lopez, Pedro; Risalde, María A.; Machuca, Isabel; Caston, Juan J.; Martínez-Peinado, Antonio; Rivero, Antonio
Abstract : Objective: To evaluate factors associated with increased serum cholesterol levels during interferon-free hepatitis C virus (HCV) therapy. Design: Prospective longitudinal study. Methods: HIV-infected patients who started and successfully completed interferon-free therapy for chronic HCV infection were included. Patients were treated using 2 different regimens, based on the clinician's opinion: sofosbuvir and ledipasvir (SOF/LDV), or paritaprevir coadministered with ombitasvir and dasabuvir (PrOD). Both total cholesterol and low-density lipoprotein cholesterol were evaluated at baseline, weeks 1, 2, 4, 8, end of treatment (EOT), weeks SVR4, SVR12, and SVR24. Results: The study population therefore comprised 85 patients reaching sustained virological response, 42 (49.4%) of whom were treated with SOF/LDV, and 43 (50.6%) with PrOD. Patients using SOF/LDV was showed a higher increase on both total cholesterol and low-density lipoprotein cholesterol during treatment period than those receiving PrOD. Analyzing the overall increase from baseline to weeks 1, 2, 4, 8, and EOT, choice of HCV regimen was associated with differential increases in total cholesterol during therapy. After EOT, no differences were found between SOF/LDV and PrOD with respect to total cholesterol. Conclusions: Our study suggests that the differential timing of the restoration of cholesterol metabolism in HIV/HCV genotype 1 coinfected patients achieving sustained virological response is not mediated by HCV clearance but depends on the drug combination used. Abstract : Supplemental Digital Content is Available in the Text.